Alleviating poverty through Islamic microfinance: factors and measures of financial performance, and roles of Islamic values and financial policies - Ginanjar, Adhitya; Salina, Kassim (Academic Research Publishing Group, 2019)
Indonesia has a strong presence of microfinance sector with the number of Islamic Microfinance Institutions (IMFIs) estimated to be around 5,000 currently. Microfinance is an effective tool in alleviating poverty in Indonesia due to the limited access to financial services by the poor who accounted for approximately 96 million Indonesians (or 37% of the total population), living on less than USD 1.90 a day. In the absence of collateral and steady income, the poor are considered too risky to be given credit facilities by the formal financial services providers and living in remote areas has also limited their access to formal financial services. This study aims to examine the poverty alleviation efforts from the perspective of the IMFIs in view of their direct involvement in the process and having rich information about financial issues facing the borrowers. The managers also understand about financial inclusion agenda as well as financial guidelines and regulations issued by the relevant authorities. A total of 34 managers of Baitulmaal Wa Tamwil (BMTs), which registered under the Sharia Cooperative Centre (INKOPSYAH) are taken as respondents from the Jakarta, Bogor, Depok, Tangerang and Bekasi (JABODETABEK) areas. The first instrument was a survey questionnaire, and the second one was an in-depth interview to outline data related to the model design. The findings of this research are expected to contribute to better decision-making for the BMTs to further enhance its role in alleviating poverty. The findings also elaborate several dimensions to improving financial inclusion among the poor including providing financial services, implementing Islamic principles, significant policies, community-based framework concept and training financial education. This research highlights the need for a variety of strategies to warrant success of poverty alleviation efforts by BMT.